The synergistic benefits of physical and cognitive exercise in schizophrenia: Promoting motivation to enhance community effectiveness - Choi, Jimmy (Schizophr Res Cogn, 2019)
Emerging research highlights the potential cognitive benefits of physical exercise (PE) programs for schizophrenia (SCZ). The few recent efficacy studies that examined augmenting cognitive training (CT) with PE suggest superior effects of the combination. The next step is to consider strategies to enhance adherence in real-world settings if this type of combined treatment is going to be effective. We present the first community effectiveness data for PE and CT that included a motivationally-enhancing, self-determined approach to exercise, in lieu of participant payment. Eighty-five outpatients with schizophrenia attending an intensive outpatient program were randomized to 18 h of either (A) self-determined PE regimen with choice from a menu of different activities; (B) tablet-based neurofeedback CT focused on processing speed (PS) and working memory (WM), or (C) a time-matched combination of PE and CT. Assessments were conducted at baseline, post, and follow-up (2 mo). All groups improved in WM from baseline to post, with greatest gains in the PE only group. At follow-up, cognitive gains originally observed in the PE-only group disappeared, while the PE + CT group evidenced improvements in WM and psychotic symptoms. Notably, attrition for PE was only 7%. Our data shows that combining PE and CT leads to lasting effects that are superior to those of either intervention alone. The low PE drop-out rate suggests a self-determined approach to the exercise regimen was tolerable, and may be an important component of future community implementation efforts.